Tinjauan Kritis Perkembangan Metode Penelitian Etnografi dan Etnometodologi - Fadila Fadila; Leli Yulifar (Universitas Batanghari Jambi, 2023)
The background of this research is because people still have limited knowledge of ethnographic and ethnomethodological research methods in a study. The problems discussed in the writing are: 1. How is the development of ethnographic research and ethnomethodological research? and 2. When did ethnographic research and ethnomethodological research begin? The research method used is the historical method through the stages of heuristics, criticism, interpretation and historiography. Data collection techniques through library research techniques (library research) are carried out through literature studies and several reference sources such as journals, articles, books and others. The aim of the research is to describe the development of ethnographic and ethnomethodological research and to provide understanding and introduction to ethnographic and ethnomethodological research to the government. The research results found that ethnographic research methods were better known by the wider community than ethnomethodological research methods.